Evaluation of the Implementation of 'SIPS-MUDA' School Payment Information System - Fantika Febry Puspitasari; Taufiq Satria Mukti; Silvia Mudy Safitri; Aini Mahfudhoh (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
Globalisation has a significant influence on the world of education. The emergence of technology supports the implementation of services in providing school financial accountability through a digital payment information system. Therefore, this research aims to review the effectiveness and efficiency of the application of SIPS-MUDA in providing payment information using a case study with a mixed-method approach. Data was collected through interviews, observations, documentation, and surveys. Meanwhile, the data were analysed using John Cresswell's model analysis technique. The results showed that the school payment information system effectively controlled misinformation and omission of human error factors related to the data. A survey of 46 parents also indicated that more than 80% agreed on the effectiveness and efficiency of the implementation of SIPS-MUDA. This was based on the validity of payment information, task completion, time behaviour, and customer satisfaction. In conclusion, the application of SIPS-MUDA can be categorised as very effective in providing school payment information services. Virtual accounts are a recommendation for manual input constraints, and schools can utilise bank CSR funds in cooperation.